THE DETECTION OF LEAKS FROM TAPACURÁ DAM, BRAZIL - Villar, Heldio; Antonino, Antônio Celso Dantas; Lima, Ricardo de Andrade; Menezes, Marco Otávio; Lira, Carlos Alberto Brayner de Oliveira; Bandeira, Jefferson Vianna; Viana, Afonso; Plata-Bedmar, António; García-Agudo, Edmundo (Águas Subterrâneas, 2000)
One of the many applications of stable isotope analyses is in hydrological studies. As the isotope concentration of elements in water vary as a result of fractionation due to physico-chemical processes, each water has its own “fingerprints”, so that identification of its origin is made possible. This technique has been used in the investigation of the possible leaks through the geologic formation underneath the Tapacurá Dam, near Recife, Brazil. Samples were collected from the reservoir and from several collection points downstream. These samples have been analysed for their deuterium, 18O and 13C concentrations. The comparison between results from these analyses indicated that water from the reservoir and from the other collection points had distinct origins. These findings were corroborated from standard chemical analyses and tracer studies, thus pointing to the absence of any significant underflow at the Tapacurá Dam